Official bias and match results in the United Rugby Championship: Much ado about nothing? - Dawson, P.; Downward, P.; Hogan, V.; Massey, P. (Journal of Sports Sciences, 2025)
This paper explores the factors associated with official bias and its association with match outcomes. Data are drawn from 2,032 matches of the international rugby club competition, the `United Rugby Championship` (URC) spanning the 2003-2004 to 2020-2021 seasons. Analysis including and excluding games whose attendance was affected by the COVID-19 reveals no evidence that disciplinary sanction is associated with match outcomes. Estimates also show that there is no association between the nationality of the on-field official being shared by any of the teams and sanction or match outcome. However, it is identified that having a home nationality Television Match Official (TMO) is associated with an increase in the incidence of away team sanction. The results support the case for neutral TMOs.